PENERAPAN MODEL PBL (PROBLEM BASED LEARNING) BERBASIS LKPD DIGITAL LIVEWORKSHEET UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 3 DI SD DJAMA’ATUL ICHWAN SURAKARTA PADA MATA PELAJARAN MATEMATIKA MATERI PENGUKURAN PANJANG DAN BERAT PADA TAHUN AJARAN 2024/2025 - Devi Guswindrayani; Nailina Najuba; Raeza Pradeka Rahmawati; Rusnilawati; Chamzi Rahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of third-grade students at SD Djama’atul Ichwan Surakarta in the subject of Mathematics, specifically on the topic of length and weight measurement, through the implementation of the Problem Based Learning (PBL) model integrated with digital student worksheets (LKPD) via the Liveworksheet platform. The research applied a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The subjects were 28 third-grade students. The results showed an improvement in learning outcomes, as evidenced by the average score increase from 59.50 in the pre-cycle to 70.28 in cycle I, and further to 78.75 in cycle II. Additionally, the percentage of students who achieved mastery learning rose significantly from 32% to 89%. These findings indicate that the PBL model supported by digital LKPD using Liveworksheet is effective in enhancing students’ learning outcomes and active participation in the learning process.